Self and social regulation social interaction and the development of social understanding and executive functions - Sokol, Bryan W.; Muller, Ulrich; Carpendale, Jeremy; Young, Arlene; Iarocci, Grace (Oxford University Press, 2010)
Does social interaction play a role in the development of executive function or, more generally, self-regulation? If it does play a role, what forms of social interaction facilitate the development of executive function? In this book, the contributors address these questions.